2011
DOI: 10.1016/j.bbadis.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel blocking as a therapeutic strategy for Alzheimer's disease: The case for isradipine

Abstract: Alzheimer’s disease is the most devastating neurodegenerative disorder in the elderly, yet treatment options are severely limited. The drug development effort to modify Alzheimer’s disease pathology by intervention at beta amyloid production sites has been largely ineffective or inconclusive. The greatest challenge has been to identify and define downstream mechanisms reliably predictive of clinical symptoms. Beta amyloid accumulation leads to dysregulation of intracellular calcium by plasma membrane L-type ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 104 publications
(151 reference statements)
2
95
0
Order By: Relevance
“…The mechanism of neuroprotection is linked to selective vulnerability of substantia nigra pars compacta neurons that preferentially express L‐type calcium channels. Neuroprotective effects of isradipine are achieved at the plasma concentration that is obtained within the safe dose range for human administration10, 11 and consistent with the tolerable dosage identified in our phase II study of isradipine in PD (STEADY‐PDII) 12. Isradipine is the most potent of the clinically available Cav1.3 DHPs and has excellent central nervous system penetration suggesting it is the optimal DHP to target this novel mechanism of neuroprotection 13, 14…”
Section: Introductionsupporting
confidence: 66%
“…The mechanism of neuroprotection is linked to selective vulnerability of substantia nigra pars compacta neurons that preferentially express L‐type calcium channels. Neuroprotective effects of isradipine are achieved at the plasma concentration that is obtained within the safe dose range for human administration10, 11 and consistent with the tolerable dosage identified in our phase II study of isradipine in PD (STEADY‐PDII) 12. Isradipine is the most potent of the clinically available Cav1.3 DHPs and has excellent central nervous system penetration suggesting it is the optimal DHP to target this novel mechanism of neuroprotection 13, 14…”
Section: Introductionsupporting
confidence: 66%
“…Among non-APOE4 carriers, nilvadipine also improved short-term cognitive functions [106]. Another dihydropyridine CCB, isradipine, conferred neuroprotective effects in vitro [107], and also attenuated the levels of hyperphosphorylated tau and suppressed autophagy of tau [108].…”
Section: Antihypertensive Drugsmentioning
confidence: 96%
“…Additionally, understanding the BIN1 roles in other pathways possibly associated with AD might help us to elucidate its role in AD pathogenesis. A recent study showed that BIN1 increases the risk of AD by interacting with tau protein and by affecting neurofibrillary tangles (60)(61)(62). However, further studies are needed to determine the mechanism of interaction between BIN1 and tau, and neurofibrillary tangles, which might be promising for novel treatment approaches.…”
Section: Discussionmentioning
confidence: 99%